Music Express foundation stage : Learning intentions activities, songs, stories, pictures, recordings, videoclips - Hickman, Sally; Nicholls, Sue; Scott, Patricia (London : A&C Black, 2006)
resource on music at foundational stage (for ages three to five). It comprises a book, audio compact disc and CD-ROM. Arranged in themes which Early Years providers use, the content includes songs, stories, rhymes, dances and games. There are videoclips of the activities in use with young children.
Includes CD / CD-ROM.
Keywords: Music -- Study and teaching (Elementary).; Elementary education in spesific subjects -- Music